Genome-wide analyses of cassava Pathogenesis-related (PR) gene families reveal core transcriptome responses to whitefly infestation, salicylic acid and jasmonic acid - Irigoyen, Maria L.; Garceau, Danielle C; Bohórquez Cháux, Adriana; Becerra López Lavelle, Luis Augusto; Pérez Fons, Laura; Fraser, Paul D.; Walling, Linda L. (Springer, 2020)
Background: Whiteflies are a threat to cassava (Manihot esculenta), an important staple food in many tropical/ subtropical regions. Understanding the molecular mechanisms regulating cassava’s responses against this pest is crucial for developing control strategies. Pathogenesis-related (PR) protein families are an integral part of plant immunity. With the availability of whole genome sequences, the annotation and expression programs of the full complement of PR genes in an organism can now be achieved. An understanding of the responses of the entire complement of PR genes during biotic stress and to the defense hormones, salicylic acid (SA) and jasmonic acid (JA), is lacking. Here, we analyze the responses of cassava PR genes to whiteflies, SA, JA, and other biotic aggressors. Results: The cassava genome possesses 14 of the 17 plant PR families, with a total of 447 PR genes. A cassava PR gene nomenclature is proposed. Phylogenetic relatedness of cassava PR proteins to each other and to homologs in poplar, rice and Arabidopsis identified cassava-specific PR gene family expansions. The temporal programs of PR gene expression in response to the whitefly (Aleurotrachelus socialis) in four whitefly-susceptible cassava genotypes showed that 167 of the 447 PR genes were regulated after whitefly infestation. While the timing of PR gene expression varied, over 37% of whitefly-regulated PR genes were downregulated in all four genotypes. Notably, whitefly-responsive PR genes were largely coordinately regulated by SA and JA. The analysis of cassava PR gene expression in response to five other biotic stresses revealed a strong positive correlation between whitefly and Xanthomonas axonopodis and Cassava Brown Streak Virus responses and negative correlations between whitefly and Cassava Mosaic Virus responses. Finally, certain associations between PR genes in cassava expansions and response to biotic stresses were observed among PR families. Conclusions: This study represents the first genome-wide characterization of PR genes in cassava. PR gene responses to six biotic stresses and to SA and JA are demonstrably different to other angiosperms. We propose that our approach could be applied in other species to fully understand PR gene regulation by pathogens, pests and the canonical defense hormones SA and JA.